HEREDITARY ANGIONEUROTIC EDEMA: CASE FROM PRACTICE - I.S. Razikova; N.D. Dustbabaeva; N.P. Aydarova; V.F. Baybekova; B. T. Qudratillaeva; Sh.B. Ishmukhamedova (Scholar Express Journals, 2023)
Hereditary and acquired angioedema are a complex problem in clinical allergology, their prevalence has not been studied enough. Hereditary angioedema is rare and accounts for no more than 2% of all cases of angioedema; in the general population, its hereditary nature is detected with a frequency of 1:10,000–1:150,000 people. In the Republic of Uzbekistan, this pathology has not been studied enough, statistical records are not kept. Considering the foregoing, our center set itself the goal of studying the prevalence of hereditary and acquired angioedema nosologies in the republic makes not more than 2% of all angioedema cases, in the total population hereditary angioedema is detected with the rate of 1:10000 (1:1500000 persons. There are three forms of the disease: hereditary angioedema type I, hereditary angioedema type II and estrogen-dependent edema (type III). The first two forms are due to a genetically determined absolute or relative deficiency of the C1 inhibitor, in the third form its concentration and function are not changed. Hereditary angioedema, unfortunately, today is not curable, despite the achievements of modern medicine, however, in the case of a full history taking, targeted diagnosis and timely treatment, it is possible to achieve significant positive dynamics in the course of the disease. In medical science, little experience has been accumulated in this nosology, which prompted us to publish a publication on such a rare clinical case.
Keywords: Angioedema; complement; C1-exterase inhibitor